Biochemical and molecular changes associated with heteroxylan biosynthesis in Neolamarckia cadamba (Rubiaceae) during xylogenesis - Zhao, Xianhai; Ouyang, Kunxi; Gan, Siming; Zeng, Wei; Song, Lili; Zhao, Shuai; Li, Juncheng; Doblin, Monika S.; Bacic, Antony; Chen, Xiao-Yang; Marchant, Alan; Deng, Xiaomei; et al. (Frontiers in Plant Science, 2014)
Wood, derived from plant secondary growth, is a commercially important material. Both cellulose and lignin assembly have been well studied during wood formation (xylogenesis), but heteroxylan biosynthesis is less well defined. Elucidation of the heteroxylan biosynthetic pathway is crucial to understand the mechanism of wood formation. Here, we use N. cadamba, a fast-growing tropical tree, as a sample to analyze heteroxylan formation at the biochemical and molecular levels during wood formation. Analysis of the non-cellulosic polysaccharides isolated from N. cadamba stems shows that heteroxylans dominate non-cellulosic polysaccharides and increase with xylogenesis. Microsomes isolated from stems of 1-year-old N.cadamba exhibited UDP-Xyl synthase (UXS) and xylosyltransferase (XylT) activities with the highest activity present in the middle and basal stem regions. To further understand the genetic basis of heteroxylan synthesis, RNA-Seq was used to generate transcriptomes of N. cadamba during xylogenesis. The RNA-seq results showed that genes related to heteroxylan synthesis had higher expression levels in the middle and basal part of the stem compared to the apical part. Our results describe the heteroxylan distribution and heteroxylan synthesis trait in N. cadamba and give a new example for understanding the mechanism of heteroxylan synthesis in tropical tree species in future.